Քահանայական սպասաւորութեան խնդիրը Հայ Առաքելական Սուրբ Եկեղեցու Վրաստանի եւ Իմերեթի թեմում (ԺԹ. դարի երկրորդ կէս — Ի. դարի առաջին տասնամեակ) - Գրիգորեան, Վարդիթեր (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Священнический вопрос всегда был в центре внимания епархиальных властей Грузино-имеретинской епархии Армянской Апостольской Церкви. Для решения этого вопроса в годы предводительства епископа Аристакеса Седракянца (1883—1889) и архиепископа Геворка Суренянца (1894—1904) были предприняты активные шаги. Priestly issues have always been in the focus of attention of the diocesan authorities of the Georgian-Imeretian Diocese of the Armenian Apostolic Church, and for their solution, active steps were taken during the years of the diocesan rule of Bishop Aristakes Sedrakyants (1883—1889) and Archbishop Gevorg Surenyants (1894—1904).
Keywords: History